Chapter Curriculum InstitutionALE - Professionalization of Adult Education Institutions - Lichtenberg, Thomas (Studies on Adult Learning and Education, 2023)
Curriculum InstitutionALE is an orientation framework for strengthening Institutions of Adult Learning and Education. It provides basic guidelines for managing capacity and organisational development and suggests indicators and means of verification for organisational change and capacity development. It offers the basics for defining goals and criteria for capacity and organisational development, for collecting reliable baseline data, for designing and implementing processes of capacity and organisational development, and for assessing progress. Addressing leaders of Institutions of Adult Learning and Education and external advisors, it can be adjusted to fit various contexts and institutions across the world.